Clinical and biochemical observations on three cases of hypoxanthine-guanine phosphoribosyltransferase deficiency. Issue 3 (June 1975) - Bunn, D N; Moss, I K; Nicholls, A; Scott, J T; Snaith, M L; Watson, M R
Abstract : Clinical and enzymatic studies on two brothers with severe deficiencies of erythrocyte hypoxanthineguanine phosphoribosyltransferase (HGPRTase) are described, and are compared with similar studies of a classical case of the Lesch-Nyhan syndrome from another family. The two brothers have no neurological abnormalities, only traces of erythrocyte HGPRTase, erythrocyte adenine phosphoribosyltransferase activities approaching the high levels found in the Lesch-Nyhan patient, and similarly raised plasma and urinary concentrations of uric acid. Despite these strong biochemical similarities between the three patients, there were wide differences in the clinical case histories. In both families the enzyme deficiency appeared to be inherited as an X-linked character through asymptomatic carrier females. The relationship of HGPRTase deficiencies to the Lesch-Nyhan syndrome is discussed. Some observations relating to techniques are reported. Cellulose acetate has been found to give much better separations of labelled reaction products in low-level phosphoribosyltransferase assays than filter paper, when used as a supporting medium for electrophoresis. The analysis of hair follicles gives indications of individuals heterozygous for the enzyme deficiency, but the proportion of enzyme-deficient follicles was very small, and the test needs support from studies of other cell types. Using haemolysates, there were signs of a slow indirect conversion of hypoxanthine to inosinic acid, via inosine. Inosine appears to be labelled by a ribosyl-transfer reaction.